2022
DOI: 10.3390/biotech11030040
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological and Medical Aspects of Lactic Acid Bacteria Used for Plant Protection: A Comprehensive Review

Abstract: The use of chemical pesticides in agriculture goes hand in hand with some crucial problems. These problems include environmental deterioration and human health complications. To eliminate the problems accompanying chemical pesticides, biological alternatives should be considered. These developments spark interest in many environmental fields, including agriculture. In this review, antifungal compounds produced by lactic acid bacteria (LABs) are considered. It summarizes the worldwide distribution of pesticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 122 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…Unreasonable doses of mineral fertilizers, the use of chemical means to control plant diseases and the failure to comply with the technology of their application bring harm to the environment (Raman et al, 2022). Thus, scientists search for ecological methods of protection from the agents of crop diseases, which could be found in microbes-antagonists for the elaboration of biopreparations on their basis (Dragovoz et al, 2014;Hrabova et al, 2015;Davranov et al, 2019;Bergsma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unreasonable doses of mineral fertilizers, the use of chemical means to control plant diseases and the failure to comply with the technology of their application bring harm to the environment (Raman et al, 2022). Thus, scientists search for ecological methods of protection from the agents of crop diseases, which could be found in microbes-antagonists for the elaboration of biopreparations on their basis (Dragovoz et al, 2014;Hrabova et al, 2015;Davranov et al, 2019;Bergsma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in their application impacts the ecological equilibrium and safety of food products and is the main factor of environmental pollution (Ra man et al, 2022). Th erefore, as an alternative to chemical preparations, researchers pay great attention to the elaboration of ecologic methods of protection against crop disease agents, using microbial preparations, based on different species of microorganisms and their metabolites (Bergsma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“… Arena et al (2018) claimed that a protonated form of lactic acid inhibits the pH gradient between the outside acidic environment and the inside alkaline cytosol, dissipating the membrane potential and killing cells. LAB metabolites reported that molecules such as hydrogen peroxide, acetate, butyrate, formic acid, succinate, propionate, valerate, caproic acid, and cyclic dipeptides have potent antifungal properties ( Fazeli et al, 2004 ; Bergsma et al, 2022 ; Zapaśnik et al, 2022 ). An experiment on sourdough bread between six strains of Lactiplantibacillus plantarum showed that strain AR524 at 10 8 CFU ml –1 could remove the highest amount of DON (0.359 mg kg –1 ), and this process majorly occurred in the fermentation stage ( Cao et al, 2021 ).…”
Section: Biological Control Of Fusaria By Lactic Acid Bacteriamentioning
confidence: 99%
“…The antifungal activity of LAB results from metabolites regulated by gene expression and is considered an intraspecific trait [17]. Short-chain organic acids, bacteriocins, chitinolytic enzymes, and volatile compounds are believed to be the metabolites that inhibit fungal growth and spore germination [15,18]. Lactiplantibacillus plantarum and other lactobacilli are the most intensively studied genera of LAB in relation to their antifungal activity against Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%